Cost asymmetries in international subsidy games: should governments help winners or losers? - Neary, J (Elsevier, 1994)
I consider the optimality of export subsidies in oligopolistic markets, when home and foreign firms have different costs and the social cost of public funds exceeds unity. Subsidies are optimal only for surprisingly low values of the social cost of public funds and, if subsidies are justified, they should be higher the more cost competitive are domestic firms. These results hold under both Cournot and Bertrand competition and in a two-period perfect equilibrium with learning by doing. The results suggest that recent arguments for export subsidies are more applicable to firms which possess a ‘comparative advantage in profit shifting’.